Q: What is the value of x in the equation 2x 3y 36 when y 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x plus 3y is not an equation, it is an expression.

If you mean: 2x+3y = 6 then it is 2x+3y = 11

-2x plus 3y equals 1

To put the equation 3y - 9 = 2x in y-intercept form (y = mx + b): 3y - 9 = 2x 3y = 2x + 9 (add 9 to both sides of the equation) y = 2/3 x + 3 (divide all terms by 3) The y-intercept is the b term in the equation, which in this example is 3.

A line with equation y = mx + c has slope m (and intercept c), thus convert the given equation into this form: 2x + 3y = 18 ⇒ 3y = -2x + 18 ⇒ y = -2/3x + 6 ⇒ slope is -2/3.

Related questions

2x plus 3y is not an equation, it is an expression.

If you mean: 2x+3y = 6 then it is 2x+3y = 11

The equation 2x - 3y = 6 is a linear equation and a linear equation is always has a straight line as a graph

Solve for y.2x - 3y = 52x - 2x - 3y = -2x + 5-3y = -2x + 5-3y/-3 = -2x/-3 + 5/-3y = (2/3)x - 3/5Clearly you see that the slope is 2/3.

-2x plus 3y equals 1

2x+3y=40-2x+2y=20Since 2x does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 2x from both sides.3y=-2xDivide each term in the equation by 3.(3y)/(3)=-(2x)/(3)Simplify the left-hand side of the equation by canceling the common terms.y=-(2x)/(3)if you were solving for x It would be x=-(3y)/2

If the missing sign is minus then you have the difference of two squares so: (2x + 3y)(2x - 3y)

Actually, 2x + 3y + z is an expression, because it is a mathematical noun.

2x+3y=12 ......1st equation 3x+2y=13 .......2nd equation ____________________________________ multiplying 1stt equation by 3 and 2nd equation by 2 3x(2x+3y=12) 2x(3x+2y=13) _______________________________ now the equations become 6x+9y=36 ...3rd 6x+4y=26 ....4th by solving both equation(substractinf 4th from 3rd) we get.. 5y=10 therefore y=2 and x=3

2x+3y-5=0

To put the equation 3y - 9 = 2x in y-intercept form (y = mx + b): 3y - 9 = 2x 3y = 2x + 9 (add 9 to both sides of the equation) y = 2/3 x + 3 (divide all terms by 3) The y-intercept is the b term in the equation, which in this example is 3.

A line with equation y = mx + c has slope m (and intercept c), thus convert the given equation into this form: 2x + 3y = 18 ⇒ 3y = -2x + 18 ⇒ y = -2/3x + 6 ⇒ slope is -2/3.